Analysis of diesel particulate matter on single cylinder diesel engine using waste plastic fuel - Mohd Radzi, Mohd Rasol (2012)
This study deals with the size diameter and concentration distribution of particulate matter (PM) using single cylinder engine diesel using waste plastic disposal fuel. The experiment was devided by two. First experiment is to determine fuel characteristic and the second experiment to analyzed the size diameter and distribution of PM. The characteristic fuel is for determine affect to size diameter and concentration distribution for both fuel. For the experiment size diameter and concentration distribution of PM both fuel be test in 5 different speed which is 1200 rpm,1500 rpm, 1800 rpm, 2100 rpm and 2400 rpm. From the experiment, the result be determine is concentration of PM, dry soot(DS), soluble organic fraction (SOF) and size diameter. All the result can obtained by the calculation and analysis. The end of this analyis show the waste plastic disposal fuel is better than diesel in term produce of gas emission . where the result show waste plastic disposal fuel produce less PM ,NOx, NO, CO2, CO and O. While result for distribution of size diamete